Does the population living in Roma settlements differ in physical activity, smoking and alcohol consumption from the majority population in Slovakia? - Babinská, Ingrid; Gecková, Andrea Madarasová; Jarcuska, Peter; Pella, Daniel; Mareková, Mária; Stefková, Gabriela; Veselská, Zuzana Dankulincová; HepaMeta Team (Central European journal of public health, 2014)
BACKGROUND: Several studies have revealed a high prevalence of risk factors associated with unhealthy lifestyle among individuals with lower socioeconomic status. In Slovakia, one of the most socially and health-disadvantaged groups is the Roma minority. The aim of this study is to explore differences in physical activity, smoking and alcohol consumption between the population living in Roma settlements and the majority population in Slovakia. METHODS: Data from the cross-sectional epidemiological HepaMeta study conducted in Slovakia in 2011 were used. The sample consisted of 452 Roma (mean age = 34.7; 35.2% men) and 403 non-Roma (mean age = 33.5; 45.9% men) respondents. The differences in health-related behaviour between the population living in Roma settlements and the majority population were analysed using logistic models separately for males and females. RESULTS: These data show a clear difference between the population living in Roma settlements and the majority population with regard to leisure-time physical activity (only in women) and smoking, although not alcohol consumption. The prevalence of leisure-time physical activities such as walking or some other type of sport was significantly lower among Roma women than among non-Roma women. Men and women living in Roma settlements are more likely to smoke on a daily basis and they are heavier smokers in comparison with the majority population. HepaMeta study did not find differences in alcohol consumption between the Roma and non-Roma men. However, Roma women reported less frequent recent drinking and binge-drinking of 6 or more doses of alcohol on a single occasion. CONCLUSION: The higher prevalence of unhealthy lifestyle activities among Roma seem to contribute to these inequalities in cardiovascular diseases morbidity and mortality in comparison with the majority population.
Keywords: dospělí; Sex Distribution; Smoking; zdravotnické přehledy; odds ratio; Female; charakteristiky bydlení; Prevalence; rozložení podle pohlaví; Adult; ženské pohlaví; pití alkoholu; průřezové studie; mladý dospělý; Life Style; životní styl; Adolescent; kouření; Alcohol Drinking; pohybová aktivita; Slovakia; lidé; Humans; Risk Factors; prevalence; zdravé chování; Residence Characteristics; Cross-Sectional Studies; venkovské obyvatelstvo; Male; Romové; Socioeconomic Factors; Young Adult; rizikové faktory; Roma; Motor Activity; lidé středního věku; Slovenská republika; socioekonomické faktory; Health Surveys; mužské pohlaví; Middle Aged; mladiství; Rural Population; Odds Ratio; Health Behavior